Fatigue analysis of sign-support structures during transportation under road-induced excitations. (1st June 2018) - Arabi, Saeed; Shafei, Behrouz; Phares, Brent M.
Graphical abstract: Highlights: The fatigue-induced damage in Dynamic Message Sign (DMS)-support structures is investigated. This study includes both field investigations and finite-element simulations for fatigue analysis. Strains and stresses at various truss members and joints are found under road-induced excitations. The extent of damage that DMS-support structures can experience during transportation is predicted. Abstract: Dynamic Message Signs (DMSs) are increasingly used in highways as an effective means to communicate time-sensitive information with motorists. To ensure the long-term performance of DMSs, it is critical to ensure that the truss structures that hold them can resist not only extreme loading events, but also fatigue induced by service loads. The existing studies, however, are primarily focused on the loads that DMS-support structures experience during their service life and neglect the potential contribution of stresses induced during the transportation of them from the fabrication site to the location of installation. As a result, the potential damage that this important category of structures may sustain during transportation had remained largely unknown. To investigate this aspect, a comprehensive field test and numerical study were conducted. For field investigation, one span of a four-chord, overhead sign-support structure was instrumented to perform a short-term structural health monitoring. In addition, detailed finite element simulations were conducted to obtain an in-depth understanding of the potential modes of damage under the excitations induced by the road profile. The outcome of this study is expected to contribute to evaluating the extent of fatigue and structural vulnerability of DMS-support structures during transportation.